Sport-for-employability as an innovative practice in addressing youth underemployment in sub-Saharan Africa - Burnett, Cora (Frontiers in Sports and Active Living, 2023)
Youth unemployment reflects the lack of economic growth and prosperity for many nations in sub-Saharan Africa where the average age of the population is estimated to be 24 years in 2050. The study generates insights informed by preliminary findings of an ambitious 6-month government-funded “youth employment program” in South Africa. The paper reports on qualitative data emanating from two field visits per organization providing the baseline of this national project as the researcher had been tasked to develop the monitoring, evaluation, and learning (MEL) system. About 4,000 of this population are from Special Olympics and comprise of youth with complex needs, while the baseline focus on 45 youth as part of the unified leadership initiative (partnering with a mainstream individual). The MEL system allows for a mixed-method approach, but the paper draws on narrative data obtained during field visits where 10 managers were interviewed and 47 youth interns (42.5% men and 57.5% women) took part in focus group discussions. The interview and focus group questions explored their work-related histories and profiles, current involvement with a structured program, experiences, perceptions, expectations, and pragmatic recommendations. Emerging themes and analysis report five main themes that refer to (i) personal employment histories, (ii) local embeddedness, (iii) a typology of work, (iv) program benefits, and (v) enablers and goal setting. Contextual realities shaped the agency of all research participants, but promising results show positive outcomes of soft skills associated with the level of employability and job-seeking strategies.